Enhancing teachers' pedagogical competence through the development of innovative learning tools based on the TPACK approach - Wibowo Heru Prasetiyo; Beti Indah Sari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
This community service aimed to enhance the pedagogical competence of Pancasila and Civic Education (PPKn) teachers through a TPACK-based (Technological, Pedagogical, and Content Knowledge) workshop on innovative lesson plan (Rencana Pelaksanaan Pembelajaran/RPP) development. Low pedagogical competence in lesson planning remains a persistent challenge for PPKn teachers, as evidenced by below-standard national assessment scores. The workshop engaged junior and senior high school PPKn teachers affiliated with the Indonesian Pancasila and Citizenship Education Professional Association (AP3KnI) of East Java and was delivered online through interactive methods comprising theoretical instruction, learning strategy demonstrations, and guided hands-on practice. Evaluation results confirmed the workshop's effectiveness: mean pedagogical competence scores increased from 6.14 to 11.57, yielding an N-Gain of 63% (classified as "strong") and a large effect size (Cohen's d = 2.046). These findings demonstrate that short-term, structured TPACK-based interventions can produce significant and measurable gains in teacher competence, even in an online format. The workshop model is replicable and scalable, offering a practical reference for professional teacher associations and educational stakeholders seeking to advance technology-integrated instructional practices in 21st-century education